SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166096-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Distribution of Proppant in Multistage Fractured Horizontal Wells: A CFD Simulation Approach

Abstract: Multistage hydraulic fracturing has become the key technology for completion of horizontal and vertical wells. The perf and plug method is the most commonly used staging method. In each stage, multiple perforation clusters are used, attempting to create a separate transverse fracture at each cluster. How these clusters are placed can significantly affect both short-and long-term production performance. Simultaneous creation of multiple fractures is a cost-effective and time saving method for stimulating both v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In addition, Crespo et al [16] observed the phenomenon of uneven proppant distribution within three perforation clusters through conducting a large-scale experimental study to mimic the plug-and-perf operation, and it will be more severe in cases with higher proppant density and smaller flow rates. Bokane et al [20] used computational fluid dynamics (CFD) technique to simulate proppant transport in different perforation clusters within a single stage and to understand the phenomena of uneven proppant distribution within perforations. However, the impact of uneven proppant distribution between different clusters within a single stage on ultimate gas recovery has not been evaluated quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Crespo et al [16] observed the phenomenon of uneven proppant distribution within three perforation clusters through conducting a large-scale experimental study to mimic the plug-and-perf operation, and it will be more severe in cases with higher proppant density and smaller flow rates. Bokane et al [20] used computational fluid dynamics (CFD) technique to simulate proppant transport in different perforation clusters within a single stage and to understand the phenomena of uneven proppant distribution within perforations. However, the impact of uneven proppant distribution between different clusters within a single stage on ultimate gas recovery has not been evaluated quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental results, they found that fluid velocity and proppant properties (type and size) are the main factors affecting the uneven distribution of proppant in each perforation diameter [11,12]. Bokane et al studied the distribution of proppant in each cluster of fractures considering factors such as proppant particle size, density, fracturing fluid viscosity, and pumping displacement through large-scale laboratory experiments, and they found that high displacement, high viscosity and small particle size, and low-density proppant can improve the nonuniform sand injection effect of each cluster [13]. Yi et al used the Eulerian multiphase flow model to fit Freddy Crespo's laboratory test results, and verified the feasibility of Eulerian multiphase flow in simulating proppant migration in a wellbore [14].…”
Section: Introductionmentioning
confidence: 99%
“…21 The numerical approaches are widely applied 22 because of its advantages of revealing the internal flow mechanism of the solid-liquid two-phase and the flow details that are difficult to obtain experimentally. 23,24 To capture the physics of coal particle transport in fracturing fluid flow, the two key numerical approaches available in the literature are the Eulerian-Lagrangian method 25 and the Eulerian-Eulerian method. 24 The Eulerian method models the continuous phase by solving the mass and momentum conservation equations, and the solid phase (coal particle) is modeled by tracking particle motion using Newton's second law of motion.…”
Section: Introductionmentioning
confidence: 99%
“…24 The Eulerian method models the continuous phase by solving the mass and momentum conservation equations, and the solid phase (coal particle) is modeled by tracking particle motion using Newton's second law of motion. 25 For tracking discrete phases, the Lagrangian and Eulerian methods are coupled to analyze the particle-fluid system issues existing in industry. 26 The two most common Eulerian-Lagrangian methods used in the literature are the discrete particle method (DPM) 27 and the computational fluid dynamics-discrete element method (CFD-DEM).…”
Section: Introductionmentioning
confidence: 99%